The hive [large type] - Hornby, Gill (Thorndike Press large print core series., 2014)
It's the start of another school year at St. Ambrose. While the children are busy in the classroom, their mothers are learning sharper lessons. Lessons in friendship. Lessons in betrayal. Lessons in the laws of community, the transience of power . . . and how to get invited to lunch. The Hive is a wickedly funny and brilliantly observed story about female friendship, power plays, and the joys and perils (well, mainly perils) of trying to do one's part.